2011
DOI: 10.1590/s1413-35552011000200002
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographic activity of shoulder muscles during exercises performed with oscillatory and non-oscillatory poles

Abstract: Background: Pain and dysfunction of the shoulder complex are commonly found physiotherapy practice. These musculoskeletal

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 27 publications
(36 reference statements)
0
16
0
2
Order By: Relevance
“…Despite the intensity of the exercise with the oscillatory pole used in our study have been based on previous studies [3,5] it may be, at least partly, related to the absence of blood pressure responses during the evaluation period.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Despite the intensity of the exercise with the oscillatory pole used in our study have been based on previous studies [3,5] it may be, at least partly, related to the absence of blood pressure responses during the evaluation period.…”
Section: Discussionmentioning
confidence: 95%
“…We observed that after the exercise there was an increase in parasympathetic tone (SD1 index) 25-30 minutes after exercise compared to rest and a decrease in overall variability (SD2 index) 5-10 minutes and 10-15 minutes after exercise compared to 15 to 20 minutes after exercise. Furthermore, no significant differences were Previous studies reported that exercise with oscillatory pole is considered an isometric anaerobic exercise that provides the contraction of the muscles of the shoulder and trunk [3,5]. In this sense, during the execution of static exercise for lower limbs with 40% of maximum voluntary contraction Mitchell and cols.…”
Section: Discussionmentioning
confidence: 96%
“…Pesquisas recentes mostram efeitos positivos do uso da haste vibratória sobre os músculos do tronco e ombro [12][13][14][15][16] . Mesmo existindo alguns estudos publicados a respeito dos efeitos da haste vibratória sobre o sistema neuromuscular, estes tratam, em sua maioria, dos efeitos agudos do uso deste equipamento e não existe na literatura estudos a respeito dos efeitos do treinamento de equilíbrio com haste vibratória sobre variaveis biomecânicas da marcha de idosos.…”
Section: Discussionunclassified
“…However, based on the present results, there was no change in systolic and arterial pressure recovery after one bout of flexible pole exercise. It is believed that the intensity of the protocol exercise used in this study, that was based on previous studies, rather than the style of exercise, was the main reason for the absence of significant cardiovascular responses during the recovery phase [27]. …”
Section: Discussionmentioning
confidence: 99%
“…All exercises were performed for 15 seconds with 50–60 seconds of rest between each exercise. Three repetitions were performed for each exercise [21]. The exercises were performed with both arms on three positions: 1) with shoulders at approximately 180° of flexion with the flexible pole on the frontal plane, parallel to the ground , 2) with the shoulder on 90° of flexion with the flexible pole on the transverse plane , and 3) shoulders at 90° of flexion with the flexible pole on the sagittal plane, perpendicular to the ground.…”
Section: Methodsmentioning
confidence: 99%